Serviceology for Designing the Future Selected and Edited Papers of the 2nd International Conference on Serviceology - Maeno, Takashi; Sawatani, Yuriko; Hara, Tatsunori (Springer Japan : Imprint: Springer, 2016)
This book provides a useful overall guide to the state of the art in theory and practice of services. It can also serve as a reference book for researchers in various fields, including engineering, marketing, economics, and other disciplines. Advanced works presented here were selected from the proceedings of the Second International Conference on Serviceology (ICServ2014), held September 14-16, 2014. This book helps readers to understand serviceology, which tackles with a broad range of services, the globalization of the economy and also enhances the quality of life of local residents.